2019
DOI: 10.1016/j.scitotenv.2018.11.403
|View full text |Cite
|
Sign up to set email alerts
|

Acetate promotes microbial reductive debromination of tetrabromobisphenol A during the startup phase of anaerobic wastewater sludge bioreactors

Abstract: The detection of increasing concentrations of tetrabromobisphenol A (TBBPA) in wastewater treatment plants is raising concerns as TBBPA has been identified as a potentially toxic flame retardant. The objectives of this study were to evaluate the effect of acetate biostimulation on TBBPA microbial reductive debromination, and the response of anaerobic sludge associated microbial communities repeatedly exposed to TBBPA. Results indicate that the bulk of the microbial community did not experience significant shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 62 publications
(90 reference statements)
0
21
0
Order By: Relevance
“…Among the genera that were downregulated, Blvii28_wastewater-sludge_group has been commonly found in wastewater or wastewater treatment systems [38,39]. Researchers have indicated that this genus functions in the initial attachment during the biofilm forming process.…”
Section: Resultsmentioning
confidence: 99%
“…Among the genera that were downregulated, Blvii28_wastewater-sludge_group has been commonly found in wastewater or wastewater treatment systems [38,39]. Researchers have indicated that this genus functions in the initial attachment during the biofilm forming process.…”
Section: Resultsmentioning
confidence: 99%
“…The richness of wastewater sludge microbiomes and diversity of niches in WWTPs provide a number of different possible pathways for HFRs biotransformation in wastewater treatment systems and anaerobic digesters. Indeed, biotransformation of HFRs in wastewater sludge has been investigated at lab-, pilot-, and full-scale in numerous studies. ,,, Additionally, efforts have been made to enrich, isolate and characterize the functional HFR-transforming microorganisms in wastewater sludge. Aerobic biotransformation of HFRs in WWTPs usually occurs via oxidative transformation during aerobic treatment processes (Table ). Kim and Oh evaluated the mass balance of PBDEs in a full-scale WWTP in South Korea and concluded that a 40% mass loss of PBDEs was most likely caused by oxidative biotransformation mediated by the activated sludge microbiome; this conclusion was based on the formation of hydroxylated and methoxylated PBDEs during aerobic biological wastewater treatment .…”
Section: Fate Of Hfrs In Biological Treatment Systemsmentioning
confidence: 99%
“…In early laboratory studies, approximately 99% of TBBPA was anaerobically biotransformed by the digester sludge microbiome within 3 days . Similarly, a continuously operated anaerobic reactor inoculated with activated sludge completely debrominated >95% of TBBPA to BPA in 5 days . However, BPA is more toxic than TBBPA, and subsequent biotransformation processes that detoxify BPA are not always occurring in anaerobic reactors.…”
Section: Fate Of Hfrs In Biological Treatment Systemsmentioning
confidence: 99%
See 2 more Smart Citations